Sistem Manajemen Reservasi Ruangan di Gedung Pusat Kegiatan Mahasiswa (PKM) Universitas Bengkulu - Hijrayanti, Hikmah; Butar Butar, Federika; Oktoeberza, Widhia KZ (Rekursif: Jurnal Informatika, 2025)
The Bengkulu University Student Activities Center (PKM) requires an efficient room reservation management system to overcome manual processes that are prone to errors, delays and lack of transparency. This project aims to design and develop a web-based Room Reservation Management System using the Laravel framework, which allows students to see real-time room availability and make online reservations. This system also makes it easy for admins to manage room and reservation data systematically and avoid schedule conflicts. With the Waterfall development methodology, system design is carried out using Unified Modeling Language (UML) and testing using the Black Box Testing method. This system is expected to increase the efficiency of room management, provide information transparency, and minimize manual process obstacles, thereby supporting the effectiveness of student activities. Implementation of this system contributes to the modernization of campus administration services and optimization of PKM facilities.